Structural Barriers to Religious Freedom: A Progressive Legal Analysis of Justice Access in the Construction of Minority Worship Houses in Indonesia - Mahdiyyah Harahap, Ghina; Moreno Panjaitan, Gabriel; Intan Oktavia Br Sihite, Dhea (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
This study aims to examine the structural barriers faced by religious minority groups in Indonesia concerning the licensing of houses of worship and access to justice. Employing a qualitative approach within a socio-legal research design, the study combines normative analysis of legal regulations with empirical exploration through in-depth interviews, field observations, and document analysis. The findings reveal that administrative requirements under the Joint Ministerial Decrees No. 9 and 8 of 2006 serve as a mechanism for institutionalizing social vetoes. Residents’ approval, often framed as a neutral procedural demand, is systematically exploited to obstruct the constitutional rights of minorities. State actors such as the Religious Harmony Forum (FKUB), the Ministry of Religious Affairs, and local enforcement agencies tend to adopt a passive stance—or, at times, reinforce discriminatory practices under the guise of maintaining social order. Furthermore, court decisions that favor minority groups are frequently disregarded in practice, highlighting a gap between formal legal victories and substantive justice. The main contribution of this study lies in its integrated application of progressive legal theory and the access to justice framework, offering a critical lens on how religious discrimination is embedded not only in laws but in everyday legal institutions. The study concludes that urgent regulatory reform, the establishment of an independent appeals mechanism, and mandatory minority representation in key institutions such as FKUB are essential steps toward ensuring genuine religious freedom in Indonesia.